2018
DOI: 10.2174/1745017901814010614
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Fixed Appliance and Periodontal Status: An Updated Systematic Review

Abstract: Background:Periodontal implications of orthodontic therapy are frequent, gingival and periodontal conditions need to be evaluated for every appointment. Several studies have analyzed the effects of fixed appliance on periodontal health.Objective:To evaluate whether there is updated scientific evidence on the relationship between fixed orthodontic therapy and periodontal health.Methods:A literature search was performed using the Pubmed and Cochrane databases and manual search; the search was carried out using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 22 publications
2
29
0
8
Order By: Relevance
“…Orthodontic treatment aims to establish good functional and aesthetic occlusion and to ensure long-term preservation of oral health [1,2]. Correcting crowded teeth enables patients to better perform oral hygiene and reduces occlusal trauma [1]. However, fixed orthodontic appliances might compromise adequate oral hygiene by increasing food residues and bacterial plaque retention [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthodontic treatment aims to establish good functional and aesthetic occlusion and to ensure long-term preservation of oral health [1,2]. Correcting crowded teeth enables patients to better perform oral hygiene and reduces occlusal trauma [1]. However, fixed orthodontic appliances might compromise adequate oral hygiene by increasing food residues and bacterial plaque retention [3].…”
Section: Introductionmentioning
confidence: 99%
“…None of the studies were adjusted for possible confounding factors. A recent systematic review [1] concluded that in short term follow-ups, orthodontic appliances seem to increase general plaque accumulation and gingivitis. After long-term follow-up, however, gingival status and periodontal values trend towards normalisation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Plaque control and SRP performed before initiating pre-surgical orthodontic treatment may have temporarily suppressed inflamma- tion. However, multi-bracket devices make it difficult to clean tooth surfaces effectively 7,19) , and self-maintenance proved inadequate, with the periodontitis worsening throughout the period of active orthodontic therapy. This suggests that regular periodontal maintenance is essential during active orthodontic therapy 12,13) .…”
Section: Effect Of Active Orthodontic Therapy On Generalized Aggressive Periodontitismentioning
confidence: 99%
“…In any case, these levels of MS, return to normal after a complete removal of the orthodontic device. 4,5,6,7,8 B.S. Lim reported that the orthodontic adhesives have a greater ability to retain cariogenic streptococci in the material which constitutes the bracket.…”
Section: Introductionmentioning
confidence: 99%